Correlates of and changes in aerobic physical activity and strength training before and after the onset of COVID-19 pandemic in the UK: findings from the HEBECO study - Lion Shahab; Abigail Fisher; Phillippa Lally; Aleksandra Herbeć; Dimitra Kale; Verena Schneider (BMJ Open)
Objectives Understanding changes in moderate to vigorous aerobic physical activity (MVPA) and muscle-strengthening activity (MSA) at the start of the COVID-19 pandemic and their correlates (socio-demographics, health characteristics, living and exercise conditions and pre-pandemic MVPA/MSA) can inform interventions.Design A cross-sectional analysis of retrospective and concurrent data on MVPA/MSA.Setting An online survey in the UK.Participants 2657 adults (weighted n=2442, 53.6% women) participating in the baseline survey (29 April 2020–14 June 2020) of the HEalth BEhaviours during the COVID-19 pandemic (HEBECO) study.Primary and secondary outcome measures Meeting WHO-recommended levels for MVPA/MSA/both (vs meeting neither) during the first lockdown and changes in MVPA/MSA from before to since the COVID-19 pandemic following stratification for pre-pandemic MVPA/MSA.Results A third of adults maintained (30.4%), decreased (36.2%) or increased (33.4%) MVPA. For MSA, the percentages were 61.6%, 18.2% and 20.2%, respectively. MVPA increased or decreased by an average of 150 min/week and 219 min/week, respectively, and MSA by 2 days/week. Meeting both MSA+MVPA recommendations since COVID-19 (vs meeting neither) was positively associated with meeting MVPA+MSA before COVID-19 (adjusted OR (aOR)=16.11, 95% CI 11.24 to 23.07) and education: post-16 years of age (aOR=1.57, 95% CI 1.14 to 2.17), and negatively associated with having obesity (aOR=0.49, 95% CI 0.33 to 0.73), older age (65+ years vs ≤34 years; aOR=0.53, 95% CI 0.32 to 0.87) and annual household income of <50 000 GBP (aOR=0.65, 95% CI 0.46 to 0.91). The odds for decreasing MVPA were lower for white ethnicity (aOR=0.62, 95% CI 0.44 to 0.86), education: post-16 years of age (aOR=0.73, 95% CI 0.58 to 0.91) and access to garden/balcony (aOR=0.75, 95% CI 0.60 to 0.94), and were higher for those living in total isolation (aOR=3.81, 95% CI 2.33 to 6.23), with deteriorated psychological well-being (aOR=1.40, 95% CI 1.15 to 1.71) and conditions limiting physical activity (aOR=1.74, 95% CI 1.27 to 2.39). The odds for decreasing MSA were higher for having overweight (aOR=1.88, 95% CI 1.39 to 2.55), obesity (aOR=23.38, 95% CI 2.23 to 5.14) and being employed (aOR=1.81, 95% CI 1.34 to 2.46).Conclusion Aerobic and strength training were differently impacted during the first UK lockdown, with poorer outcomes associated with older age, lower education and higher body mass index. Targeted interventions may be required to avoid pandemic-related inequities in physical activity.